AYURVEDIC MANAGEMENT OF MEDO ROGA W.S.R. DYSLIPIDEMIA : A CASE REPORT - P.A.Ann Rose (International Journal of Applied Ayurved Research, 2018)
A 47 year old male patient of Medo Roga (dyslipidemia) came to our ayurveda hospital with increased cholesterol levels for 4 years. He leads a sedentary life style and is obese in built. Patient was under statin since 2 years before he managed with dietary restrictions around 2 years. After the intake of statin he noticed increase in sluggishness, body pain, muscle pain and slight increase in blood glucose levels. He consulted our hospital and he was treated as OPD patient for 30 days with internal medicine Patolachitrakadi kashaya. He was asked to take 48ml of freshly prepared kashaya twice daily after food. Patient responded to the treatment well .After the therapy patient felt improvement and there were remarkable decrease in lipid levels